EFEKTIVITAS KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 17 PEKANBARU - Siregar, Andika Saputra; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is: 1) determine the quality of education at Junior High School 17, Pekanbaru, and 2) determine the role of the school committee in improving the quality of education at Junior High School 17 Pekanbaru. Research by the author is using a qualitative approach. In the course of collecting data, the writer used interview, observation, and documentation. As for the analysis, the writer uses descriptive qualitative analysis techniques, the data in the form of written or spoken of observed behavior and so in this case the author seeks to conduct research that is thoroughly describe the actual state of affairs.The results of this study are: First, the quality of education at Junior High School 17 Pekanbaru can be quite good, this can be seen in terms of input, process and output. Second, the role of school committees in improving the quality of education at Junior High School 17 Pekanbaru, including: 1) As consideration giver (advisory agency): SMP Negeri 17 Pekanbaru Committee as the principal partner has given consideration in any plans and programs prepared by the schools, for example in terms of rehab facilities and buildings damaged, widen mushalla, procurement of equipment prayer (mukenah and gloves). In addition, the school committee also provided input and consideration in setting RAPBS, giving consideration in the implementation process of the management of education in schools and identify the educational resources available in the community for consideration and seconded at school. 2) As a supporter (supporting agency): the role of the school committee as a subsidiary body for implementation and improving the quality of education, especially education in SMP Negeri 17 Pekanbaru is the form of financial support, personnel, and support the mind. 3) As a control (controlling agency): SMP school committee in 17 Pekanbaru exercise control over decision making and planning education in schools, in addition to the allocation of funds and resources for the implementation of programs in schools. The school committee also perform control functions to the success of education in schools is seen from the quality of educational output. 4) as a mediator (executive agency): School Committee SMP Negeri 17 Pekanbaru in these many benefits, which in the presence of the school committee, the aspirations of the students and parents can be channeled and represented. In addition, the school has always had the support of the school committee in order to continue to improve the quality of education.Keywords: Effectiveness, School Committee, Quality of Education